Problems of Protohistoric Iran as Seen from Hasanlu - Dyson, Jr. Robert H.
Period VI (ca. 1600-1250 B.C.); Transition from Period IV to V (ca. 1250 B.C.); Period V (ca. 1250-1000 B.C.); Transition to Period IV (ca. 1000 B.C.); Period IV (ca. 1000-800 B.C.); Transition to Period III В (?750 B.C.); Hasanlu III В (?750-600 B.C.); Transition to Period III A (ca. 600 B.C.); Period III A (600-400 B.C.).